Turkey's politics : the transition to a multi-party system - Karpat, Kemal H. (Princeton legacy library., 1959)
This book discusses in full the economic, social, and cultural background of modern Turkey's political system. Beginning with a historical sketch of the problems of the Ottoman Empire that gave rise to the early reform movement, Professor Karpat describes the eventual formation of the Republic and the consequent economic and social changes and the international political developments conditioned by the Second World War. In the central portion of the book he focuses attention on postwar political developments, with special emphasis on the critical period from 1945 to 1950. Originally published in 1959. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.